2014
DOI: 10.1155/2014/210129
|View full text |Cite
|
Sign up to set email alerts
|

A Variable Precision Covering-Based Rough Set Model Based on Functions

Abstract: Classical rough set theory is a technique of granular computing for handling the uncertainty, vagueness, and granularity in information systems. Covering-based rough sets are proposed to generalize this theory for dealing with covering data. By introducing a concept of misclassification rate functions, an extended variable precision covering-based rough set model is proposed in this paper. In addition, we define the f-lower and f-upper approximations in terms of neighborhoods in the extended model and study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Therefore, in the process of evaluating the reliability of elevator equipment, we need to fully consider the interacting factors among indicators, clarify the interrelation among indicators, and build the figure of interrelation among the indicators of the reliability of elevators, which is shown in Figure 1. [6][7][8] Definition 1. Let = ( , , , ) be a knowledge expressing system, where is the universe, is the attribute set, is the attribute-values set, and is the information function.…”
Section: The Analysis Of Reliability Factor For Elevators and The Conmentioning
confidence: 99%
“…Therefore, in the process of evaluating the reliability of elevator equipment, we need to fully consider the interacting factors among indicators, clarify the interrelation among indicators, and build the figure of interrelation among the indicators of the reliability of elevators, which is shown in Figure 1. [6][7][8] Definition 1. Let = ( , , , ) be a knowledge expressing system, where is the universe, is the attribute set, is the attribute-values set, and is the information function.…”
Section: The Analysis Of Reliability Factor For Elevators and The Conmentioning
confidence: 99%
“…Some researchers extended this concept to variable precision covering based rough set model [16][17]. Algebraic properties of rough set have been widely studied by researchers [18][19][20][21][22][23][24]. Algebraic properties of variable precision rough set is discussed in this paper and it could be shown that for different classification error the set of variable precision rough sets have a lattice structure.…”
Section: Introductionmentioning
confidence: 99%